Religious gestures and secular strengths: Emerson, Nagel, and Kateb on the religious temperament - Hosseini, Reza (Religious studies, 2021)
What would happen to the reception of Emerson if one does not share his religious sentiments? I argue that appreciating Emerson does not depend upon sharing a similar attitude towards religion not only because we can discern a secular sense of wonder in his writings, as George Kateb claims, but also because his literary excellence shows us ways of wonder in the first place. Further, I show that though there is a brief exchange of similar ideas between Emerson and Thomas Nagel in the latter's engagement of ‘the religious temperament’, their responses to what they call the tremendousness of existence is fundamentally different.